Shared watercourses and water security in South Asia : challenges of negotiating and enforcing treaties - Salman, Salman M. A., 1948- (Brill research perspectives. International water law., 2018)
The monograph discusses the various challenges facing shared water resources in South Asia, and the response of most these countries, presented in their calls for water security. Consequently, negotiating new transboundary water treaties amongst South Asia's riparian countries has become a daunting task, and enforcing existing ones remains a real challenge.